2017
DOI: 10.18632/oncotarget.19487
|View full text |Cite
|
Sign up to set email alerts
|

MiR-590-3p promotes proliferation and metastasis of colorectal cancer via Hippo pathway

Abstract: Studies reported that miR-590-3p was involved in human cancer progression. However, its roles of oncogene or anti-oncogene in malignancies still remain elusive. This study was aimed to investigate the effect of miR-590-3p on the cell proliferation and metastasis via Hippo pathway in colorectal cancer (CRC). In our study, miR-590-3p was demonstrated highly expressed in CRC tissues, compared with adjacent normal tissues (P<0.05). In addition, miR-590-3p was positively associated with TNM stage and distant metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…Multivariate analysis also revealed miR‐590 as an independent prognostic factor for tumour recurrence of GC patients. Intriguingly, our findings for the functions of miR‐590 in GC were also supported by some other studies in a variety of cancers, such as colorectal cancer (CRC), cervical cancer and glioblastoma, but opposed by those in CRC and glioblastoma multiforme . Thus, our above results showed that miR‐590 might act as an oncogenic marker in GC by targeting PPM1F.…”
Section: Discussionsupporting
confidence: 88%
“…Multivariate analysis also revealed miR‐590 as an independent prognostic factor for tumour recurrence of GC patients. Intriguingly, our findings for the functions of miR‐590 in GC were also supported by some other studies in a variety of cancers, such as colorectal cancer (CRC), cervical cancer and glioblastoma, but opposed by those in CRC and glioblastoma multiforme . Thus, our above results showed that miR‐590 might act as an oncogenic marker in GC by targeting PPM1F.…”
Section: Discussionsupporting
confidence: 88%
“…Although the role of miR-590-3p in EOC has not previously been established, several studies have reported both tumorpromoting and tumor-suppressive effects of miR-590-3p in other types of cancer. For example, miR-590-3p promotes cell proliferation and invasion in T-cell acute lymphoblastic leukemia by inhibiting RB1 (6) and in colorectal cancer by targeting the Hippo pathway (7) and by promoting b-catenin signaling (32). Similarly, tumor-promoting effects of miR-590-3p were observed in glioblastoma (33).…”
Section: Discussionmentioning
confidence: 99%
“…miR-590-3p was first reported to enhance cardiomyocyte proliferation and cardiac regeneration after myocardial infarction (5). More recently, the effects of miR-590-3p on several types of cancer have been reported (6)(7)(8). Although the role of miR-590-3p in ovarian cancer is unknown, an RNA sequencing (RNA-seq) study has identified miR-590-3p as one of the miRNAs dysregulated in EOC tumors (9), suggesting its potential role in EOC development.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpressed miR-362-3p influences cell cycle arrest and reduces cell viability and proliferation in CRC cells, which is associated with the recurrence of CRC [42]. miR-590-3p accelerates cellular proliferation and metastasis via targeting the Hippo pathway, and it can predict worse clinical outcomes of CRC patients [43].…”
Section: Discussionmentioning
confidence: 99%